HUBUNGAN SHIFT KERJA DENGAN TEKANAN DARAH PADA PERAWAT DI RUMAH SAKIT CAMATHA SAHIDYA KOTA BATAM - Rusdani Rusdani; Luis Yulia (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2019)
The work of a nurse in providing nursing services is inseparable from setting working hours in a hospital, better known as work shifts. The work shift system will have a variety of positive effects, but the work shift can cause effects that are quite disturbing to the health of workers, especially as experiencing a lack of sleep. Sleep deprivation associated with shift work can affect metabolic hormones ie, decreased growth hormone production, and decreased circadian melatonin rhythms and health burdens such as metabolic disorders, obesity, diabetes, and hypertension. In addition to coronary heart disease and stroke, hypertension complications can cause heart failure, peripheral vascular disease, kidney disorders, retinal bleeding, and vision problems. This is the cause due to interference with blood pressure, as for the factors that can affect blood pressure, namely, age, sex, exercise, drugs, race, and obesity. This research is a quantitative study with an observational analytic research design with a cross-sectional approach. Subjects were nurses who worked in shifts and nurses who did not shift in Camatha Sahidya Hospital, Batam City in 2018. A total of 98 study samples were selected using the total sampling method. Data collection techniques were used to measure blood pressure. Data were analyzed with Chi-Square test analysis and processed with Statistical Product and Service Solution (SPSS). Research Results: This study shows the results, analysis of the Relationship between Work Shift and Blood Pressure in Nurses at Camatha Sahidya Hospital in Batam City in 2018 who worked without shifting pressure 8 (80%) normal blood and 2 (20%) prehypertension. While nurses who work in normal blood pressure shifts are 33 (37.5%), prehypertension is 54 (61.3%) and first-degree hypertension is 1 (1.1%). Related to the value of p = 0.035 (<0.05), then H0 is rejected and there is a relationship between work shifts and blood pressure for nurses at Camatha Sahidya Hospital in Batam City in 2018. There is a Relationship between Work Shift and Blood Pressure in Nurses at Camatha Sahidya Hospital in Batam City in 2018.